Implementation of CAPM in Determination of Stock Investment Decisions in Lq45 Index (Year 2017-2021) - Alamsyah, Sustari; Nur Isna Inayati; Fahman Nur Rahman (Dinasti International Journal of Economics, Finance & Accounting, 2022)
Errors in valuing stock securities result in losses for investors, so a careful assessment must be made so that investments are made right and profitable. The purpose of this study is to determine the stock return and risk using the CAPM method and classify and assess efficient and inefficient stocks in determining investment decisions in the 2017-2021 LQ45 index. This study uses a quantitative descriptive approach. The population in this study are companies listed on the LQ45 index. The sampling technique used purposive sampling and obtained a sample of 26 companies. The results showed that there was a negative or non-linear relationship between beta (?i) and the expected rate of return [E(Ri)]. In addition, there are 16 stocks including efficient stocks and 10 stocks including inefficient stocks. The investment decision that investors must make is to buy efficient stocks and sell inefficient stocks as soon as their value declines